A Prospective Study Conducted Among Participants Reporting Acute Febrile Illness in a Cohort of Periurban and Rural Cambodians. Issue 6 (November 2020) - Antony, Suresh J.; Chonthida, Supaprom; Luy, Malen; Hip, Phireak; Sopheab, Heng; Faix, Dennis; Blair, Patrick; Putnam, Shannon D.
Abstract : Abstract: The objective of this prospective cohort study was to assess the incidence of dengue, chikungunya, respiratory viruses, and diarrheal etiologies among periurban and rural Cambodians with confirmed acute febrile illness. During a 2-year period (2016–2017), 612 participants aged 6 months to 30 years who exhibited vector-borne febrile illness (median [interquartile range] age, 8.0 [4–11] years), in which 288 (48.0%) were female, were tested for acute dengue virus and chikungunya virus infection. A total of 67 (11.2%) clinical specimens were positive for dengue virus by either nucleic acid detection (n = 23 [34.3%]; dengue serotype 1 [n = 5] and dengue serotype 2 [n = 18]) or dengue IgM capture enzyme-linked immunosorbent assay (n = 44 [65.7%]), and only 8 specimens were both positive. Clinical presentations included fever (100%), headache (74.1%), muscle aches (27.2%), and joint pain (17.3%). Forty-two of the 612 participants were diagnosed with chikungunya (7.0%) by anti–chikungunya virus enzyme-linked immunosorbent assay (IgM) or chikungunya-specific reverse transcription polymerase chain reaction. By understanding the incidence of diseases causing morbidity and mortality in rural areas within Cambodia, mitigating strategies can be developed to reduce infections.